DEMONSTRATED INTEREST: SIGNALING BEHAVIOR IN COLLEGE ADMISSIONS. (11th February 2017) - Dearden, James A.; Li, Suhui; Meyerhoefer, Chad D.; Yang, Muzhe
Abstract : In college admission decisions, important and possibly competing goals include increasing the quality of the freshman class and making the school more selective while attaining the targeted size of the incoming class. Especially for high‐quality applicants who receive multiple competing offers, colleges are concerned about the probability that these students accept the offers of admission. As a result, applicants' contacts with admissions offices, such as campus visits, can be viewed positively by the officers as demonstrated interest in the colleges. We provide empirical evidence on the effects of demonstrated interest on admission outcomes. Specifically, we use unique and comprehensive administrative data, which include all contacts made by each applicant to the admissions office of a medium‐sized highly selective university during two admission cycles. We find that an applicant who contacts the university is more likely to be admitted, and that the effect of the contact on the probability of admission is increasing in the applicant's Scholastic Assessment Test score, particularly when the contact is costly to make. We also use a numerical example to explore policies to reduce the inequity associated with the use of demonstrated interest in admission decisions, examining in particular the subsidization of costly demonstrated interest by low‐income students. ( JEL D83, I23)